Analisa dan Optimasi Pengaruh Physical Tunning Terhadap Handover Failure Pada Jaringan 4G LTE Di Kecamatan Kuranji - Aulia, Siska; Angela, Tri Utari; Maria, Popy; Dewi, Ratna; Ramiati, Ramiati (Elektron : Jurnal Ilmiah, 2024)
Data collection has been carried out using the drivetest method to determine the quality and problems of the 4G LTE network in Kuranji District, Padang City. The aim of the research is to determine the existence of handover failure and optimize handover failure on the 4G LTE network using the physical tuning method in Kuranji District. The research method is physical tuning for network optimization planning using Atoll software. The research results obtained 2 points of handover failure; at point 1 handover failure latitude -0.9133879 and longitude 100.4189513 served by site Kuranji 3 cell id 326 sec 3 optimization of antenna tilting from 2º to 6.5º, site Kuranji cell id 55 sec 2 optimization of re-azimuth from 140º to 100º , antenna tilting from 2º to 3.5º, antenna height from 23m to 31m. At point 2 handover failure latitude -0.8906544 and longitude 100.4185787, the site serving the Belimbing cell ID 131 sector 3 overshoot occurs, the antenna is tilted from 2º to 8º and the site serving the handover failure area occurs, the Belimbing site cell ID 130 sec 2 tilts the antenna. from 2º to 8. Optimization of physical tuning is able to cover handover failure areas and increase the total performance quality value of RSRP signal strength coverage from 33.46% to 33.74%, SINR from 81.7% to 81.57%, and Throughput optimization results remain the same at 100%.